Harvesting Intensity and Aridity Are More Important Than Climate Change in Affecting Future Carbon Stocks of Douglas-Fir Forests - Robinson, Alyssa J.; Defrenne, Camille E.; Roach, W. Jean; Dymond, Caren C.; Pickles, Brian J.; Simard, Suzanne W. (Frontiers in Forests and Global Change, 2022)
Improved forest management may offer climate mitigation needed to hold warming to below 2oC. However, uncertainties persist about the effects of harvesting intensity on forest carbon sequestration, especially when considering interactions with regional climate and climate change. Here, we investigated the combined effects of harvesting intensity, climatic aridity, and climate change on carbon stocks in Douglas-fir (Pseudotsuga menziesii Mirb. (Franco)) stands. We used the Carbon Budget Model of the Canadian Forest Sector to simulate the harvest and regrowth of seven Douglas-fir stand types covering a 900 km-long climate gradient across British Columbia, Canada. In particular, we simulated stand growth under three regimes (+17%, -17% and historical growth increment) and used three temperature regimes (historical, representative concentration pathways (RCP) 2.6 and RCP 8.5). Increasing harvesting intensity led to significant losses in total ecosystem carbon stocks 50 years post-harvest. Specifically, forests that underwent clearcutting were projected to stock about 36% less carbon by 2069 than forests that were left untouched. Belowground carbon stocks 50 years into the future were less sensitive to harvesting intensity than aboveground carbon stocks and carbon losses were greater in arid interior Douglas-fir forests than in humid, more productive forests. In addition, growth multipliers and decay due to the RCPs had little effect on total ecosystem carbon, but aboveground carbon declined by 7% (95% confidence interval [ -10.98, -1.81]) in the high emissions (RCP8.5) scenario. We call attention to the implementation of low intensity harvesting systems to preserve aboveground forest carbon stocks until we have a more complete understanding of the impacts of climate change on British Columbia’s forests.